STEVENS JOHNSON SYNDROME PADA PASIEN HIV - bevi dewi citra; Raveinal masri (Universitas Fort De Kock, 2020)
Stevens Johnson Syndrome (SJS) are form of drugs hypersensitivity reaction with high morbidity besides Toxic Epidermal Necrolysis (TEN). HIV-patients are one of the population with higher risk. Its due to, in this population had multifactorial aspects and related with drug metabolism, dysregulation of the immune systems (immune hyperactivation, patients cytokine profile and CD4 cell count), oxidative stress, genetic predisposition,and viral factors. A case of female, 42 years old, who had been known as HIV patients with clinical stage 3 had Stevens Johnson Syndrome. Allegedly, it caused by antiretroviral drugs (nevirapine), which she consumed for 3 weeks. Patient also has fever and hepatitis drug induced. For the the treatment, we stopped previous combination of antiretroviral drugs immediately and replaced by another combination. Furthermore, patient also had corticosteroid therapy and others supportive treatments, such as intra venous fluid, adequate nutrition, antibiotic, antifungal and also had eyelid, oral, nose and skin treatment. Patient showed clinical improvements and and improvement of liver function test after received treatments for one week in hospital Keywords: Stevens Johnson Syndrome, HIV, antiretroviral